ECONOMETRIC ANALYSIS OF LIVESTOCK PRODUCTION IN REGIONS USING A PANEL MODEL (ON THE EXAMPLE OF SURKHANDARYA REGION) - Xasanova , Dildora (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2025)
In this thesis, the process of growing the main types of livestock products is deeply analyzed on a scientific basis using a panel data model. Also, a random effect model aimed at increasing the efficiency of livestock production in the region was studied, and proposals and recommendations for its practical application were developed.